Relationship between big five personality traits academic performance and academic stress among postgraduate students in Pakistan - Mansoor Nazir Bhatti, 1977-, author 631340; Amran Mohd. Rasli, supervisor 302319; Sekolah Perniagaan Antarabangsa Azman Hashim 617120 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Doktor Falsafah (Pengurusan )) - Universiti Teknologi Malaysia, 2019